2021
DOI: 10.12688/f1000research.27809.1
|View full text |Cite
|
Sign up to set email alerts
|

IMPORTANCE trial: a provisional study-design of a single-center, phase II, double-blinded, placebo-controlled, randomized, 4-week study to compare the efficacy and safety of intranasal esketamine in chronic opioid refractory pain

Abstract: Background:  Cancer is the second leading cause of death globally. Up to 86% of advanced cancer patients experience significant pain, while 10-20% live in chronic pain. Besides, increasing prescription of opioids resulted in 33,000 deaths in the US in 2015. Both reduce patients’ functional status and quality of life. While cancer survival rates are increasing, therapeutic options for chronic opioid refractory pain are still limited. Esketamine is the s-enantiomer of ketamine, with superior analgesic effect and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Future directions for intranasal pain management include identifying and investigating potential drug candidates, improving delivery strategies and optimizing central nervous target concentrations. Drug candidates for (co-)analgesia using an intranasal administration route under investigation include NK1-receptor antagonists [ 92 ], ketamine [ 93 ] and esketamine [ 94 ], nalbuphine [ 95 ], ketorolac [ 96 ], dexmedetomidine [ 97 ] and many more. There is also a wide variety of research on permeation-enhancing agents, mucolytic agents, muco-adhesive agents, in situ gelling agents and enzyme-inhibiting agents in the formulation of nasal drug delivery systems [ 98 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…Future directions for intranasal pain management include identifying and investigating potential drug candidates, improving delivery strategies and optimizing central nervous target concentrations. Drug candidates for (co-)analgesia using an intranasal administration route under investigation include NK1-receptor antagonists [ 92 ], ketamine [ 93 ] and esketamine [ 94 ], nalbuphine [ 95 ], ketorolac [ 96 ], dexmedetomidine [ 97 ] and many more. There is also a wide variety of research on permeation-enhancing agents, mucolytic agents, muco-adhesive agents, in situ gelling agents and enzyme-inhibiting agents in the formulation of nasal drug delivery systems [ 98 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…Approximately 10-20% of patients experience refractory cancer pain that is poorly responsive to commonly used opioids such as morphine, oxycodone, and fentanyl, or who have dose-limiting intolerable adverse effects [5,6,9]. Methadone is considered an attractive alternative in these situations [8,9,11].…”
Section: Discussionmentioning
confidence: 99%
“…Opioids, including morphine, oxycodone, and fentanyl, are cornerstones for the treatment of moderateto-severe cancer pain [4]. However, 10-20% of patients who are prescribed opioids still experience inadequate pain relief and/or intolerable adverse reactions, which can be defined as refractory pain [5][6][7]. Methadone is commonly considered an alternative opioid treatment for refractory cancer pain [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…While clinical trials examining the efficacy of esketamine for chronic pain are currently ongoing (NCT04938713, NCT05160493, NCT04847245, NCT04666623), primitive studies have reported modest improvements in outcomes relating to postoperative pain and treatment-resistant depression. [54][55][56][57] The significant variability in existing protocols and the lack of direct comparisons prohibit the conclusion of an optimal dose from the literature, particularly for vulnerable populations, which remains a vital area of research needed to increase the safety of SDKIs and improve the robustness of guidelines. 11,14,37 Surveys of pain clinics in France, South Korea, and the Netherlands have demonstrated this variability between practices, including the dose, duration, and monitoring facilities, but they report that serious adverse events are rare.…”
Section: Introductionmentioning
confidence: 99%